2022
DOI: 10.3389/fpsyg.2022.869687
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Study of Educators’ Experience After a Year of the COVID-19 Pandemic

Abstract: This phenomenological study investigated educators’ lived experiences of teaching online in higher institutions in Malaysia. Data, which was generated through semi-structured interviews with 20 lecturers from three universities in the country, was analysed based on the thematic analysis approach guided by the Technological, Pedagogical, and Content Knowledge (TPACK)-self-efficacy framework. The findings revealed that after a year of teaching online, the potential of technology has been acknowledged by the educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“…Pearson's correlation coefficient was at the level of the outlook (pre-sample) 0.46, slightly lower than the correlation coefficient after gaining experiences of practices (post sample), which reached 0.49, and both at the significance level 0.01, indicating the strength of the direct relationship between the PU and the AU at the sample level (pre-survey and post-sample). These results are consistent with Alqahtani & Alturkey (2018), Annamalai et al, (2022) , they demonstrated a relationship between PEOU of the TAM2 with experiences. The use and ease of use of technology positively impacted attitudes towards technology and agreed with the study results (Chen et al,2020, Khan et al, 2017 that faculty members who had difficulties using the BB system had had negative attitudes towards continuing to use and benefit from it (Elfeky, & Elbyaly, 2023).…”
Section: Resultssupporting
confidence: 92%
“…Pearson's correlation coefficient was at the level of the outlook (pre-sample) 0.46, slightly lower than the correlation coefficient after gaining experiences of practices (post sample), which reached 0.49, and both at the significance level 0.01, indicating the strength of the direct relationship between the PU and the AU at the sample level (pre-survey and post-sample). These results are consistent with Alqahtani & Alturkey (2018), Annamalai et al, (2022) , they demonstrated a relationship between PEOU of the TAM2 with experiences. The use and ease of use of technology positively impacted attitudes towards technology and agreed with the study results (Chen et al,2020, Khan et al, 2017 that faculty members who had difficulties using the BB system had had negative attitudes towards continuing to use and benefit from it (Elfeky, & Elbyaly, 2023).…”
Section: Resultssupporting
confidence: 92%
“…Pearson's correlation coefficient was at the level of the outlook (pre-sample) 0.46, slightly lower than the correlation coefficient after gaining experiences of practices (post sample), which reached 0.49, and both at the significance level 0.01, indicating the strength of the direct relationship between the PU and the AU at the sample level (pre-survey and post-sample). These results are consistent with Alqahtani & Alturkey (2018), Annamalai et al, (2022) , they demonstrated a relationship between PEOU of the TAM2. The use and ease of use of technology positively impacted attitudes towards technology and agreed with the study results (Chen et al,2020, Khan et al, 2017 that faculty members who had difficulties using the BB learning management system had had negative attitudes towards continuing to use and benefit from it.…”
Section: Recommendationsupporting
confidence: 92%
“…Meaning making becomes an important focus of scientific enquiry in itself, in the sense that, though subjective in nature, it enables for the mapping, understanding, and analysis of human behaviour in these contexts. In education, and in the post-secondary sector in particular, the interpretivist paradigm is increasingly used to frame research into management of change, student affairs, and pedagogical transformation (Annamalai et al, 2022;Sabapathy, 2022).…”
Section: Broad Interpretivist Stancementioning
confidence: 99%